2005
DOI: 10.1111/j.1365-294x.2005.02484.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective sweeps and intercontinental migration in the cosmopolitan moss Ceratodon purpureus (Hedw.) Brid.

Abstract: The moss Ceratodon purpureus has long been used as a model system in plant development and physiology. However, the molecular population genetics of the species remains virtually unexplored. In this study, we used population genetic analyses of DNA sequence data from three unlinked loci (atpB-rbcL spacer, adk, and phy2) to examine biogeographical patterns in a global sample of this species. The three loci differed significantly in mutation frequency spectra and implied population structure. Pairs of haplotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
97
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 51 publications
(52 reference statements)
8
97
2
Order By: Relevance
“…As a first step toward understanding the genetic basis of these phenotypic differences, we generated recombinant progeny from a cross between isolates of C. purpureus from Ithaca, New York, and Otavalo, Ecuador. Taxonomically these populations belong to different subspecies (Burley and Pritchard 1990), although in previous molecular population genetic analyses we found no genealogical support for this arrangement (McDaniel and Shaw 2005). Here we describe widespread segregation distortion in the progeny of a cross between these two populations, which we suggest results from spore mortality.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…As a first step toward understanding the genetic basis of these phenotypic differences, we generated recombinant progeny from a cross between isolates of C. purpureus from Ithaca, New York, and Otavalo, Ecuador. Taxonomically these populations belong to different subspecies (Burley and Pritchard 1990), although in previous molecular population genetic analyses we found no genealogical support for this arrangement (McDaniel and Shaw 2005). Here we describe widespread segregation distortion in the progeny of a cross between these two populations, which we suggest results from spore mortality.…”
mentioning
confidence: 56%
“…Development and analysis of molecular markers: Genomic DNA was extracted from sterile protonemal tissue from the two parents and all of progeny, using a cetyl trimethyl ammonium bromide extraction, described in McDaniel and Shaw (2005), modified for 1-ml extractions using a Genogrinder 2000 bead shaker (SPEX CertiPrep, Metuchen, NJ). The DNA was resuspended in 30 ml of TE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocrusts are assemblages of lichens, bryophytes, algae, cyanobacteria, fungi, and microfauna that form on and stabilize dryland soil surfaces (reviewed by Belnap and Lange 2003;Rosentreter et al 2016;Seppelt et al 2016). One way in which biocrusts are different from plant and animal communities is that they may not be strongly dispersal-limited due to the existence of small propagules such as spores that can plausibly disperse across long distances, even continent to continent (Muñoz et al 2004;McDaniel and Shaw 2005). Consequently, there are multiple biocrust species that have multi-continental distributions or broad ranges within a single continent.…”
Section: Introductionmentioning
confidence: 99%
“…DNA studies based on population genetic analyses using three unlinked loci to examine biogeographical patterns by McDaniel & Shaw (2005) showed that in Ceratodon purpureus "Australasian haplotypes were more closely related to northern hemisphere haplotypes than to haplotypes found in the equatorial regions. Collectively these data suggest that long distance migration within the northern hemisphere and Australasian regions is common (relative to mutation rate) and that migration between these two regions, potentially via equatorial populations, is more frequent than migration among equatorial populations".…”
Section: Family Ditrichaceaementioning
confidence: 99%